Posted by **Kyler** on Wednesday, March 3, 2010 at 3:03pm.

prove 2csc(2x)= csc(x)^2tanx

## Answer this Question

## Related Questions

- math (trig) - Prove: sin^2(x/2) = csc^2x - cot^2x / 2csc^2(x) + 2csc(x)cot(x) On...
- trig - prove the identity: csc x-1/csc x+1 = cot^x/csc^x+2 csc x+1
- trig - Prove the identity sin squared 0 with line/2 = csc zero with line -cot ...
- trig - verify : [sec(x) / csc(x) - cot(x)] - [sec(x) / csc(x) + cot(x)] = 2csc(x...
- trig - prove: cos*2x=csc*2x-2/csc*2x
- trig - For each expression in column I, choose the expression from column II to ...
- trig 30 - For csc^2 A-1/cot A csc A, what is the simplest equivalent trig ...
- precalculus - 1.csc^2x-1/csc^2x=cos^2x 2.1/1-cosx+1/1+cosx=2csc^2x 3.sinxcosy+...
- Prove trig identity - Prove the following trigonometric identity: (sec^2x-1)(csc...
- Math - Prove :cosx-cosy= -2sin(x+y/2)sin(x-y/2) Prove: 2cot-2tanx= 4-2sec^2x / ...